ÙØ¹Ø§Ù„ÙŠØ© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø¥Ù…Ù„Ø§Ø¡ Ù„Ù„Ø·Ù„Ø§Ø¨ ÙÙ‰ ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±ØªÙ‡Ù… ÙÙ‰ Ø§Ù„ÙƒØªØ§Ø¨Ø© - Muhammad Riadhi (Lughatu Ad-Dhat, 2020)
ABSTRACT This study aims to determine the differences in learning outcomes for students before and after receiving treatment using the dictation method. This research was conducted in Dar es Salaam major high school year 2019/2020 study. The population in this study was students of the second semester of Dar Al-Salam Al-Kubra Al-Islamiyya Intermediate School for the 2019/2020 academic year. The sample consists of two classes, namely, the second semester, the natural sciences as an experimental class, and the second semester, the social sciences as a control class. This type of pre-experimental research with pre-test and post-test design. This research variable consists of independent variables, which are spelling learning. While the dependent variable is the ability to write Arabic language skills. Hypothesis testing consists of two stages, which are (1) using the techniques of descriptive hypothesis testing. (2) Using the t-test, previously tested to find out normal. Â Â Â Â Â Â Â The results showed a significant difference, as indicated by the research hypothesis that there is a significant difference between the increase in writing skills of the treatment students. And after. Â Keyword: teaching spelling and writing skills